Acquisitions, Multinationals and Wage Dispersion - Fredrik Heyman; Patrik Gustavsson Tingvall; Fredrik Sjöholm (Research Institute of Industrial Economics (IFN), 2006)
Multinational firms pay relatively high wages. Less is known about the wage structure within multinational and non-multinational firms. We examine the impact of acquisitions on wage dispersion in Sweden using a large matched employer-employee data set. Foreign acquisitions of Swedish firms increase wage dispersion by increasing wages for high-skilled workers. The positive impact is concentrated to CEOs and managers, whereas other groups are either negatively affected or not affected at all. The impact on high-skilled workers wages seems to be caused by the acquisition rather than the ownership itself, since ownership changes from foreign to Swedish result in similar increases.
Keywords: C23; F23; J31; 330; FDI; Multinational Companies; Foreign Ownership; Wage-Dispersion; Skill Groups; Matched Employer-Employee Data; Multinationales Unternehmen; Direktinvestition; Lohnniveau; Lohnstruktur; Qualifikation; Schätzung; Schweden